Immulina as an Immunostimulatory Supplement: Formulation and Pharmacological Studies - Li, Yusheng; Ji, Nan; Wang, Minia; Pugh, Nirmal D.; Khan, Ikhlas A.; Tan, Chalet (Planta Medica, 2023)
Immulina is a commercially available extract of Arthrospira platensis enriched with bacterial lipoproteins that acts as a potent Toll-like receptor 2 agonist. However, the immunostimulatory effect of Immulina is not well understood in vivo. Here, to devise an Immulina formulation suitable for in vivo oral gavage dosing, Immulina nanosuspension was prepared and freeze-dried to yield lyophilized nano-Immulina, which had an average particle size of around 300 nm and fully retained the bioactivity as a Toll-like receptor 2 agonist. Compared to the regular Immulina powder, lyophilized nano-Immulina notably accelerated the dissolution in aqueous media. Immulina nanosuspension was found to stimulate the production of proinflammatory cytokines in murine bone marrow-derived dendritic cells and macrophages. The immune response to Immulina was investigated in healthy mice by longitudinally monitoring the phagocytic activity of circulating neutrophils as a surrogate marker. Following daily oral ingestion of Immulina nanosuspension (10 mg/mouse/day), the phagocytic activity of circulating neutrophils was significantly elevated, suggesting an important mechanism for Immulina to enhance innate immunity.
Keywords: Arthrospira platensis; Phormidiaceae; Immulina; TLR2; dissolution; neutrophil; phagocytosis